1998
DOI: 10.1038/sj.gt.3300770
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced gene expression in mouse lung by prolonging the retention time of intravenously injected plasmid DNA

Abstract: The effect of retention time of plasmid DNA in mouse lung cholesterol-based cationic liposomes to retain the plasmid on the level of transgene expression after intravenous DNA in the lung. The level and patterns of gene expression administration was examined. Using CMV driven obtained appeared similar to those seen in animals transexpression system with luciferase gene as a reporter and fected by DNA-liposome complexes. These results sugpreinjection of free cationic liposomes into the animal as gest that prolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(37 citation statements)
references
References 23 publications
1
36
0
Order By: Relevance
“…Interestingly, the large increase in luciferase activity was obtained with either DOTAP/pCMV␤n or DOTAP/pCLuc complexes used as the first dose. These results are similar to those obtained by pre-injecting cationic lipids and subsequently either naked DNA 34 or DNA/lipid complexes. 35 A possible explanation is that aggregates between DNA complexes and serum proteins are trapped in lung capillaries and thereby retain the DNA complexes injected later.…”
Section: Figure 6 Identification Of Transfected Lung Cells In Vivo Fosupporting
confidence: 87%
“…Interestingly, the large increase in luciferase activity was obtained with either DOTAP/pCMV␤n or DOTAP/pCLuc complexes used as the first dose. These results are similar to those obtained by pre-injecting cationic lipids and subsequently either naked DNA 34 or DNA/lipid complexes. 35 A possible explanation is that aggregates between DNA complexes and serum proteins are trapped in lung capillaries and thereby retain the DNA complexes injected later.…”
Section: Figure 6 Identification Of Transfected Lung Cells In Vivo Fosupporting
confidence: 87%
“…During the first hour, there was little change in this distribution, except a progressive NP release from lungs to liver and spleen. Two reasons can explain this biodistribution pattern (17). The first one is a nonspecific electrostatic NP interaction with the negative charges displayed by plasmatic membranes of capillary endothelial cells, such as sulfated proteoglycans and glycosylaminoglycans.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was shown that intravenous administration of naked plasmid DNA produced certain amount of gene expression in the liver (8) and the lung (9), although efficiency of this process is relatively low. Song et al (9) reported that pretreatment of cationic liposomes (DOTAP) enhanced transfection efficiency of systemically injected naked plasmid DNA (50 g/20 g of a mouse) into mouse lung. They proposed that pretreated cationic liposome play a role in formation of transient microembolization in pulmonary capillary beds and prolong retention time of naked plasmid DNA that may enhance gene transfer efficiency due to providing longer time to plasmid DNA to contact with host cells.…”
Section: Discussionmentioning
confidence: 99%